Work as a cure for mental illnesses? Opportunism and seeking ways in psychology and psychiatry in the first decades of state socialism in Hungary. Issue 2 (3rd April 2019) - Lászlófi, Viola
ABSTRACT: In Hungary, until the end of the 1940s, there were two main established methods of occupying the mentally ill who were fit for work. From the end of the nineteenth century, a lesser number of patients underwent work therapy in mental asylums, whereas the others were treated with so-called family therapy (otherwise known as the heterofamilial system), exploiting the capacities of families in the countryside. As an important part of this, the mentally ill helped in housekeeping and agricultural work. However, following the political and ideological turn of 1948, the latter form of treatment became debated, and then it was gradually superseded. Parallel to this process, work therapy came to be the most popular type of treatment for mental illnesses, as work formed the basis of the ideology of the communist state, and thus, healing through work harmonized with the general tendencies of the era. This article examines texts related to work therapy published in neurological–psychiatric and psychological journals and monographs between 1954 and 1964. However, although work therapy appeared to be the "handmaiden of ideology, " and even though it was supposed to fulfil a particular role, in reality, the role and perception of work therapy were a lot more complicated.